Comparative Study of Equivalent Static Analysis and Dynamic Response Spectrum Analysis on 5-Storey Mall Building in Magelang - Sutantra Hartono; Yosafat Aji Pranata (Universitas Islam 45, 2026)
The Aloon-Aloon Mall Magelang is a five-story building located in an earthquake-prone zone due to the meeting of the Eurasian and Indo-Australian Plates. This condition requires a structural design that meets earthquake resistance standards. However, there is no specific study related to the seismic response of the building based on local conditions. Therefore, this study is important to evaluate the performance of structures against earthquake loads in order to improve safety and reduce potential losses. Earthquake-resistant buildings are buildings that are designed and constructed with the aim of minimizing damage from earthquakes. This research aims to determine the performance of structures against earthquake loads based on SNI 1726:2019 regulations. The evaluation process is carried out with 3-dimensional modeling of buildings using ETABS software. This research analyzes the seismic response of a 5-storey mall building in Magelang City using the equivalent static analysis method and spectrum response. Structural modeling was conducted using ETABS and SAP2000, focusing on the deformation and internal forces in beams and columns due to earthquake loads. The analysis results based on both static equivalent and spectrum response programs were conducted to compare the two methods used. Based on the analysis, the response spectrum analysis resulted in a larger dislacement in the x-direction of 29.85 mm compared to the equivalent static analysis of 24.95 mm. Magelang Mall is stable to the earthquake loads that occur and there is no need to repair the structure.